Serum Leptin Level in Obese and Non-Obese Women with Polycystic Ovary Syndrome and Its Relation to Insulin Resistance - Jaya Kushwah; Kavitarati Dharwadkar; Jaideep Khare; Ashish Jain; shrikant chandrakar; Archana Sharma Pandey (International Journal of Pharma and Bio Sciences, 2022)
Obesity, Insulin resistance, and distorted endocrine predominantly ovarian functions are likely to take place in PCOS. These manifestations are associated with advancement of age and gradual accumulation of adiposity. Leptin seems to be directly related to obesity by maintaining energy homeostasis with decreased food intake and increased energy expenditure. Leptin is a polypeptide that is produced by the white adipose tissue. Leptin hormone is associated with obesity. It is regarded as a body weight regulatory hormone. The Serum levels of leptin differ depending upon the body fat stores, more stores of fat leads to higher leptin level in blood. In the circulation increased leptin level acts on hypothalamic leptin receptors to reduce appetite and food intake. This feedback mechanism is working normally, in non-obese individuals but in obese subjects, this feedback mechanism is faulty. Present study included 60 (30 obese & 30 non-obese) women diagnosed with PCOS by the Rotterdam criteria 2003 and 30 healthy women as control group. Leptin levels were measured along with measurement of fasting blood glucose, lipid profile, fasting insulin. PCOS women had significantly higher serum leptin (25.33 ± 3.48 & 22.94 ± 2.21) levels in obese and non-obese PCOS women compared to controls (17.81 ± 4.55). Leptin was significantly correlated with BMI (p < 0.0001). Fasting blood glucose (89.47 ± 6.44 & 104.8 ± 4.79) and insulin (33.75 ± 1.81 & 14.37 ± 1.47) levels were considerably high in PCOS subjects compared to control females (98.6 ± 4.18) (8.24 ± 1.03). High serum leptin, and insulin levels together with increased insulin resistance were found in obese PCOS women, suggesting that high leptin levels could be a characteristic of the obese PCOS phenotype.